Coached, Coordinated, Enhanced Neonatal Transition (CCENT): protocol for a multicentre pragmatic randomised controlled trial of transition-to-home support for parents of high-risk infants. Issue 7 (7th July 2021) - Orkin, Julia; Major, Nathalie; Esser, Kayla; Parmar, Arpita; Couture, Elise; Daboval, Thierry; Kieran, Emily; Ly, Linh; O'Brien, Karel; Patel, Hema; Synnes, Anne; Robson, Kate; et al.
Abstract : Introduction: Having an infant admitted to the neonatal intensive care unit (NICU) is associated with increased parental stress, anxiety and depression. Enhanced support for parents may decrease parental stress and improve subsequent parent and child outcomes. The Coached, Coordinated, Enhanced Neonatal Transition (CCENT) programme is a novel bundled intervention of psychosocial support delivered by a nurse navigator that includes Acceptance and Commitment Therapy-based coaching, care coordination and anticipatory education for parents of high-risk infants in the NICU through the first year at home. The primary objective is to evaluate the impact of the intervention on parent stress at 12 months. Methods and analysis: This is a multicentre pragmatic randomised controlled superiority trial with 1:1 allocation to the CCENT model versus control (standard neonatal follow-up). Parents of high-risk infants (n=236) will be recruited from seven NICUs across three Canadian provinces. Intervention participants are assigned a nurse navigator who will provide the intervention for 12 months. Outcomes are measured at baseline, 6 weeks, 4, 12 and 18 months. The primary outcome measure is the total score of the Parenting Stress Index Fourth Edition Short Form at 12 months. Secondary outcomes include parental mental health, empowerment and health-related quality of life for calculation of quality-adjusted life years (QALYs). A cost-effectiveness analysis will examine the incremental cost of CCENT versus usual care per QALY gained. Qualitative interviews will explore parent and healthcare provider experiences with the intervention. Ethics and dissemination: Research ethics approval was obtained from Clinical Trials Ontario, Children's Hospital of Eastern Ontario Research Ethics Board (REB), The Hospital for Sick Children REB, UBC Children's and Women's REB and McGill University Health Centre REB. Results will be shared with Canadian level III NICUs, neonatal follow-up programmes and academic forums. Trial registration number: ClinicalTrials.gov Registry (NCT03350243 ).